Occurrence of Cryptosporidium spp. oocytes in artificial beaches of Itaipu Lake, Paraná, Brazil - Snak, Alessandra; Soares, Pedro Rodrigo Hillesheim; Silva, Erton Gomes da; Sereno, Mallú Jagnow; Garcia, Felipe Gustavo; Silva, Marcia Benedita de Oliveira; Osaki, Silvia Cristina (Semina: Ciências Agrárias, 2017)
Cryptosporidiosis is an emerging zoonosis that causes many outbreaks worldwide. Its main route of transmission is the consumption of contaminated water or food. In Brazil, data on to the occurrence of cryptosporidiosis in animals and in humans are scarce; thus, it is important to determine the occurrence of Cryptosporidium sp. and to identify possible sources of water and food contamination in order to prevent the disease and, consequently, preserve of human health. From July/2011 to March/2012, five liters of water were collected in 10 different locations from eight artificial beaches of Itaipu Lake, Paraná, in a total of 40 samples. In two other small beaches of the lake, water was also collected from two different sites of each beach, given their size and because they were made up of water from different sources. Samples were analyzed by the modified Ziehl-Neelsen technique and nested-PCR (nPCR). All samples were negative in the modified Ziehl-Neelsen; only one (2.25%) sample was positive in nPCR. These results indicate that PCR is a more sensitive technique for the identification of Cryptosporidium in water samples. In this study, it was not possible to identify the species involved and, thus, the source of infection. Water contamination by Cryptosporidium oocytes can be caused by livestock kept near waterways, and by the people who use the place for recreational purposes. These results demonstrate risk for people who use the lake. Care should be determined to prevent the transmission of this important zoonosis.